Analisis Kesulitan Membaca Permulaan Peserta Didik Kelas I Di SDN 26 Ampenan - Aulia Azizah Rahman; Darmiany Darmiany; Ketut Sri Kusuma Wardani (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aims to analyze various beginning reading difficulties experienced by students, to find out the factors that hinder students in beginning reading difficulties, and to find out solutions to overcome students' initial reading difficulties in grade I SDN 26 Ampenan. This research is a qualitative descriptive study. This research was conducted at SDN 26 Ampenan involving grade 1 students at SDN 26 Ampenan. Data collection techniques in this study are using interviews, observation and documentation. The results showed that 47.6% of the subjects had difficulty reading at the beginning. Based on these results, it can be seen that the initial reading level of class I students at SDN 26 Ampenan is classified as